Measurement of the production cross section for a Higgs boson in association with a vector boson in the [Eta] → WW [ast] → lvlv channel in pp collisions at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Helary, Louis; Krishnan, Anjali; Kugel, Andreas; Napolitano, Fabrizio; Schöning, André; Schultz-Coulon, Hans-Christian; Spieker, Thomas; et al. (Physics letters, 2019)
A measurement of the Higgs boson production cross sections via associated WH and ZH production using H → WW* → lvlv decays, where l stands for either an electron or a muon, is presented. Results for combined WH and ZH production are also presented. The analysis uses events produced in proton-proton collisions collected with the ATLAS detector at the Large Hadron Collider in 2015 and 2016. The data correspond to an integrated luminosity of 36.1 fb(-1) recorded at a centre-of-mass energy of 13 TeV. The products of the H → WW* branching fraction times the WH and ZH cross sections are measured to be 0.67(-0.27)(+0.31)(stat.)(-0.14)(+0.18)(syst.) pb and 0.54(-0.24)(+0.31)(stat.)(-0.07)(+0.15)(syst.) pb respectively, in agreement with the Standard Model predictions.